Achievement and Demographics of Home School Students: 1998 - Lawrence M. Rudner (Arizona State University, 1999)
This report presents the results of the largest survey and testing program for students in home schools to date. In Spring 1998, 20,760 K-12 home school students in 11,930 families were administered either the Iowa Tests of Basic Skills (ITBS) or the Tests of Achievement and Proficiency (TAP), depending on their current grade. The parents responded to a questionnaire requesting background and demographic information. Major findings include: the achievement test scores of this group of home school students are exceptionally high--the median scores were typically in the 70th to 80th percentile; 25% of home school students are enrolled one or more grades above their age-level public and private school peers; this group of home school parents has more formal education than parents in the general population; the median income for home school families is significantly higher than that of all families with children in the United States; and almost all home school students are in married couple families. Because this was not a controlled experiment, the study does not demonstrate that home schooling is superior to public or private schools and the results must be interpreted with caution. The report clearly suggests, however, that home school students do quite well in that educational environment.